COMPARISON OF THE MATERNAL, FETAL, AND NEONATAL OUTCOME OF ELECTIVE AND EMERGENCY CESAREAN SECTION AT A TERTIARY CENTER - JYOTI SAINI; SAWAI SINGH LORA; DEEPIKA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Cesarean section is one of the most performed surgical procedures in the world and it carries high morbidity and mortality in comparison to vaginal delivery. The present study was conducted for evaluating the maternal and neonatal outcomes and complications in pregnant women who underwent elective versus emergency cesarean section so that appropriate measures can be taken to decrease morbidity and mortality soon. Methods: Cross-sectional comparative hospital-based study carried out at Zanana Hospital Jaipur from January 2022 to December 2022. There were 400 patients enrolled in the study 200 in elective and 200 in emergency cesareans selected randomly. Ethical approval was obtained from the ethical committee and informed consent was taken from the patients Results: The emergency cesarean section was significantly more as compared to an elective cesarean section in women in the age group 19–25 years and >35 years. Most of the cesarean sections in multipara were elective as compared to the relatively more emergency cesarean sections in nullipara. It was observed that 26.5% (52/200) of women had fetal complications. Out of them, 92.4% of underwent emergency cesarean section. About 65.5% (131/200) of participants had intra-operative complications. Out of these 62.5% (82/131) had adhesions, 17.5% (23/131) had difficult extraction, and 18.3% (24/131) had postpartum hemorrhage. Out of them, 83.3%% (20/24) occurred during emergency cesarean as compared to 16.7% (4/24) in elective cesarean. Conclusions: Maternal and fetal complications were significantly higher in the emergency cesarean section as compared to the elective cesarean section group.